THE EFFECT OF BRANCH CONNECTION POINT ON HYDRAULIC MODE OF BRANCHED OIL PIPELINE - Якимів, Йосип Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The influence of the branch connection point on the fluid flow rate in the branch and in mainline segments was investigated. The problem is solved using the head balance equations which describe fluid supply to the pipeline end and to the end of mainline diversion. The algorithm and software for hydraulic calculation of branched pipeline were developed, which allow determining the flow rate in the branch and in the segments of the mainline.